Implementasi Pengelolaan Rumah Susun Sederhana Sewa di Rusunawa Sombo Kota Surabaya - Qodriya, Lailatul; Megawati, Suci (Publika, 2024)
The management of simple flats for rent is an additional stage of organizing flats. In Surabaya, the management of simple rental flats is regulated in Surabaya Mayor Regulation number 93 of 2023. In the management of Rusunawa Sombo, there are several problems such as, residents whi are not in accordance with the requirements, which is are having a car, lack of staff, and many residents who violate the rules. The purpose of this research is to describe the implementation of the management of simple rental flats in Rusunawa Sombo, Surabaya. The method used is descriptive qualitative. The focus of this research uses the implementation model by Donald Van Meter and Carl Van Horn which has six indicators. The results showed that the implementation of the management of simple rental flats in Rusunawa Sombo Surabaya City as stipulated in Surabaya Mayor Regulation number 93 of 2023 has been running well. However, there are some obstacles that must be improved, such as the lack of UPTD Rusunawa Sombo field technical implementation staff, the weakness of supervision from UPTD Rusunawa Sombo staff, and residents who still commit many violations. Based on the research results, suggestions that can be given are 1) UPTD Rumah Susun and DPRKPP should conduct anuual evaluations of residents, 2) UPTD immediately added UPTD field technical staff in Rusunawa Sombo, 3) It is expected to immediately realize the improvement of physical conditions in the Sombo Rusunawa building, 4) It is expected that UPTD Rusunawa Sombo staff take firm action against residents who violate the rules.